Adapting Compassionate Mind Training into guided self-help for parents of autistic children - Kemp, Francesca Georgina (2024)
Background: Parents of autistic children (PAC) are at increased risk of psychological distress, including parental stress, shame and self-criticism. Poor parental mental health can adversely affect parent-child interactions and their attachment relationship, in a transactional manner. There is a lack of evidence-based PAC-specific interventions focusing on reducing their psychological distress. Furthermore, PAC experience multiple barriers to accessing direct psychological interventions provided by health services. Compassion Focused Therapy (CFT) is a recommended transdiagnostic intervention for high shame and self-criticism and is potentially applicable for use as preventative guided self-help with PAC. Cross-sectional research has shown that increased PAC self-compassion is associated with increased well-being and reduced psychological distress. There is limited research around the use of CFT with PAC. No PAC-specific CFT self-help resources are available.